Gender Violence during the Pandemic:: narratives and practices supporting women in the digital environment (Comunicação & Inovação, 2025)
This article aims to reflect on gender-based violence during the pandemic in order to answer the following question: how have communication and its technologies worked to combat violence against women in Brazil? As a methodology, we used exploratory research, with a technical procedure of case study and documentary survey in a qualitative approach. The object of study is the Maria da Penha Virtual application, developed by the Center for Law and Technology Studies at UFRJ. The app aims to speed up the request for protective measures for women in situations of violence.